Efficacy and safety of brivaracetam for partial-onset seizures in 3 pooled clinical studies. (19th July 2016) - Ben-Menachem, Elinor; Mameniškienė, Rūta; Quarato, Pier Paolo; Klein, Pavel; Gamage, Jessica; Schiemann, Jimmy; Johnson, Martin E.; Whitesides, John; McDonough, Belinda; Eckhardt, Klaus
Abstract : Objective: To assess the efficacy, safety, and tolerability of adjunctive brivaracetam (BRV), a selective, high-affinity ligand for SV2A, for treatment of partial-onset (focal) seizures (POS) in adults. Methods: Data were pooled from patients (aged 16–80 years) with POS uncontrolled by 1 to 2 antiepileptic drugs receiving BRV 50, 100, or 200 mg/d or placebo, without titration, in 3 phase III studies of BRV (NCT00490035, NCT00464269, and NCT01261325, ClinicalTrials.gov, funded by UCB Pharma). The studies had an 8-week baseline and a 12-week treatment period. Patients receiving concomitant levetiracetam were excluded from the efficacy pool. Results: In the efficacy population (n = 1, 160), reduction over placebo (95% confidence interval) in baseline-adjusted POS frequency/28 days was 19.5% (8.0%–29.6%) for 50 mg/d ( p = 0.0015), 24.4% (16.8%–31.2%) for 100 mg/d ( p < 0.00001), and 24.0% (15.3%–31.8%) for 200 mg/d ( p < 0.00001). The ≥50% responder rate was 34.2% (50 mg/d, p = 0.0015), 39.5% (100 mg/d, p < 0.00001), and 37.8% (200 mg/d, p = 0.00003) vs 20.3% for placebo ( p < 0.01). Across the safety population groups (n = 1, 262), 90.0% to 93.9% completed the studies. Treatment-emergent adverse events (TEAEs) were reported by 68.0% BRV overall (n = 803) and 62.1% placebo (n = 459). Serious TEAEs were reported by 3.0% (BRV) and 2.8% (placebo); 3 patients receiving BRV and one patient receiving placebo died. TEAEs in ≥5% patients taking BRV (vs placebo) were somnolence (15.2% vs 8.5%), dizziness (11.2% vs 7.2%), headache (9.6% vs 10.2%), and fatigue (8.7% vs 3.7%). Conclusions: Adjunctive BRV was effective and generally well tolerated in adults with POS. Classification of evidence: This analysis provides Class I evidence that adjunctive BRV is effective in reducing POS frequency in adults with epilepsy and uncontrolled seizures.